Organizational approaches to cost management of ferroalloy enterprises - Колесник, Валерія Миколаївна (Technology audit and production reserves, 2015)
The article deals with the actual problem of improving the cost management of domestic ferroalloy enterprises. An important element of this research is the analysis of the existing model of cost management at ferroalloy enterprises whose main disadvantage is the lack of clearly defined place and responsibility centre for search the alternative raw materials, especially taking into account the specificity of the industry and the large number of their own waste that can be considered separately as a potential raw material. It is indicated that to determine the effectiveness of cost management of ferroalloy enterprises, ways and methods of increasing this efficiency, it is required to build such a model of cost management, which would allow one to identify the existing level of management efficiency, single out the problem issues of existing management model, include the ways to increase the efficiency of management and would be aimed at improving the efficiency of using all kinds of resources. Consideration of resource saving, particularly resource saving measures, capable to reduce the costs of ferroalloy enterprises, must serve as an important link of general cost management model. We have suggested the improved model of cost management of ferroalloy enterprises, considering that cost management must be carried at the strategic, tactical and operational levels, and cost management functions must be complex and should be implemented within the specified model in certain sequence. In the model proposed by the author the need to introduce more effective measures possible to use the waste of ferroalloy production is taken into account. It has been found out that the model of cost management of ferroalloy enterprises should be aimed not only at manufacturing products in due time and within the prescribed volumes, taking into account the rationing of basic raw materials, but also at the largest possible reduction in costs due to cheaper, alternative raw materials for production of ferroalloys, as their own production waste should be regarded as potential raw materials.